Counter‐ion insertion of chloride in Mn3O4 as cathode for dual‐ion batteries: A new mechanism of electrosynthesis for reversible anion storage. Issue 3 (13th March 2020) - Jiang, Heng; Ji, Xiulei
Abstract: Irreversible reductive insertion of Zn 2+ transforms Mn3 O4 such that the resulting Zn0.2 Mn3 O4 exhibits highly reversible storage properties of chloride ions, thus rendering Zn0.2 Mn3 O4 an excellent cathode of aqueous dual‐ion batteries. With Zn 2+ trapped, Zn0.2 Mn3 O4 delivers the chloride‐storage capacity over 200 mAh/g at an average potential of 1.6 V vs Zn 2+ /Zn by reversibly forming a new ionic compound equivalent to Zn0.2 Mn3 O4 Cl1.7 . Electrochemical quartz crystal microbalance results suggest chloride as the primary charge carrier in the reversible oxidative anion insertion. The Mn3 O4 anion‐hosting cathode couples with Zn metal anode in a full‐cell dual‐ion battery, demonstrating stable cycling in practical pouch cells with an energy density of 150 Wh/kg based on the mass of both electrodes. Abstract : Counter‐ion insertion of chloride in Mn3 O4 as cathode for dual‐ion batteries: a new mechanism of electrosynthesis for reversible anion storage. Research Highlight: Reversible chloride storage in Zn‐ion‐trapped Mn3 O4 exemplifies a generic electrosynthesis methodology, that is, counter‐ion insertion mechanism, where irreversible ion trapping in hosts transforms their electrochemical properties of storing counter‐ions of the opposite electrical charge as battery electrodes.